One of our kind ebook - Yoon, Nicola (2024)
#1 New York Times bestselling author Nicola Yoon’s daring new work of dystopian horror is a propulsive satire set in an all-Black gated community. For fans of The Sellout and Erasure, with a shocking ending you’ll never see coming, Jodi Picoult calls it "Brilliant, provocative, seminal....Your book club will be discussing this one for DAYS.” Jasmyn and King Williams move their family to the planned Black utopia of Liberty, California hoping to find a community of like-minded people, a place where their growing family can thrive. King settles in at once, embracing the Liberty ethos, including the luxe wellness center at the top of the hill, which proves to be the heart of the community. But Jasmyn struggles to find her place. She expected to find liberals and social justice activists striving for racial equality, but Liberty residents seem more focused on booking spa treatments and ignoring the world’s troubles.  Jasmyn’s only friends in the community are equally perplexed and frustrated by most residents' outlook. Then Jasmyn discovers a terrible secret about Liberty and its founders. Frustration turns to dread as their loved ones start embracing the Liberty way of life.  Will the truth destroy her world in ways she never could have imagined? A gripping thriller with wry, razor-sharp social commentary, One of Our Kind explores the ways in which freedom is complicated by the presumptions we make about ourselves and each other.